การนิเทศการศึกษากับการพัฒนาวิชาชีพ - บุณยรัตพันธุ์ มาลินี (วารสารศิลปศาสตร์ มหาวิทยาลัยอุบลราชธานี, 2016)
การศึกษาเป็นเครื่องมือสำคัญในการพัฒนาคน ประเทศใดที่ประชากร มีความรู้ มีการศึกษาย่อมส่งผลต่อการพัฒนาประเทศ การจัดการศึกษาต้องให้ความสำคัญต่อผู้เรียน พัฒนาผู้เรียนอย่างเต็มศักยภาพ จากผลการทดสอบ O-Net และผลการทดสอบของ PISA พบว่าเด็กไทยอ่านภาษาไทยไม่รู้เรื่อง คิดวิเคราะห์ไม่ได้ซึ่งอาจเป็นผลมาจากการสอนของครู ผู้บริหาร ผู้เกี่ยวข้องกับการจัดการศึกษาจะต้องหาความรู้ใหม่ๆมาให้กับครู ต้องพัฒนาครูผู้สอนเพื่อจัดการเรียนการสอนให้มีประสิทธิภาพ สิ่งที่จะช่วยพัฒนาครูในด้านการจัดการเรียนการสอนคือการนิเทศการศึกษา ซึ่งเป็นการช่วยเหลือ แนะนำครูให้สามารถปรับปรุงการสอนซึ่งส่งผลต่อสัมฤทธิ์ของผู้เรียน การนิเทศการสอนภายในโรงเรียนเป็นกิจกรรมย่อยของการนิเทศการศึกษาเป็นการจัดการนิเทศโดยบุคลากรในโรงเรียน และครอบคลุมการพัฒนาบุคลากร หรือการพัฒนาวิชาชีพ ซึ่งมีความสำคัญต่อการพัฒนาคุณภาพการศึกษาภายในโรงเรียน การพัฒนาวิชาชีพแบบ PBSE Model เป็นการพัฒนาวิชาชีพที่เน้นผลการจัดการเรียนการสอนมากกว่า กระบวนการพัฒนาวิชาชีพครู มี 6 ขั้น ได้แก่ 1) ขั้นเตรียมความพร้อมของครู 2) ขั้นการร่วมมือเบื้องต้น 3) ขั้นกำกับดูแลเบื้องต้น 4) ขั้นทบทวนระหว่างกระบวนการ 5) ขั้นกำกับดูแลระยะที่สอง 6) ขั้นทบทวนสรุป PBSE Model เป็นรูปแบบการนิเทศเพื่อการพัฒนาวิชาชีพ รูปแบบการนิเทศแบบนี้เน้นความสัมพันธ์ระหว่างครูกับผู้นิเทศโดยครูเป็นผู้ริเริ่มอยากพัฒนาวิชาชีพของตน การที่บุคคลเริ่มต้นด้วยความสมัครใจจะทำให้งานเริ่มต้นที่ดี เมื่อเริ่มต้นดีก็จะนำไปสู่ผลลัพธ์ที่ดี Supervision of Education and Professional Development Education is an important device for human development. Knowledgeable and educated population in any country affects the overall development of a country. Educational management must emphasize the development of learners’ full range potential. The results of the O-Net and the PISA examinations revealed that Thai students did not understand what they read and could not think critically, probably because of the teachers’ low teaching competence. School administrators and those who are responsible for educational management, therefore, must introduce new knowledge and teaching techniques to teachers to help them enhance their teaching effectiveness. The supervision of education is crucial for developing teachers’ instruction since it assists and guides teachers to improve their instruction which will cause the enhancement of student achievement. The supervision of instruction in a school is a sub-activity of the supervision of education, actually is carried on by the school staff and includes the staff development or the professional development which is essential for the development of the educational quality in a school. The PBSE model for professional development emphasizes the development of the instructional outcome rather than the development of the teaching profession process. The model consists of six steps: 1) teacher preparation 2) initial collaboration 3) initial monitoring 4) mid-cycle review 5) secondary monitoring 6) summative review. The PBSE model is used as one of the supervision models for professional development which emphasizes the teacher and the supervisor relations. The teacher initiates the desire to develop his/her own profession. One’s intentional and willing start results well beginning of work and its fruitful outcome.